Effectiveness of Endoparsitoid Wasp AenasiusArizonensis (Girault) as a Successful Bio-Control of Cotton Mealy Bug, PhenacoccusSolenopsis Tinsley, in Khartoum State, Sudan. - Nawal, Ahmed Mohamed; Awad, KhalafAlla Taha; Abubaker, Haroun Mohamed Adam (Journal of Agronomy Research, 2019)
The objective of this study was to evaluate the effectiveness of endophagous Encyrtid parasitic wasp Aenasiusarizonensis (Girault) (Hymenoptera, Chalcidoidea), as a natural enemy for controlling the Mealybug, Phenacoccussolenopsis Tinsley (Hemiptera: Pseudococcidae). Where a Randomized Complete Block Design (RCBD) was adopted. Both, field survey and Laboratory experiments were conducted to study some biological characteristics of the parasitoid A. arizonensis. The results of field study revealed that, the parasitioid was available most of the year, and was highly effective on adults and last larval instar of the mealy bug, P. Solenopsis, with a total percentage of parasitism of 31.26%. While the laboratory results showed that, the duration from oviposition to adult emergence were similar for both male and female. Longevity of male was 23± 2.33 days and female 23.37±1.89 days. Mean daily fecundity in terms of number of Parasitized hosts /female / day ranged from 20 to 24. The sex ratio was 1:1.6 for the male and female in the progeny. Generally, a mass rearing of this parasitoid, with a conservation and augmentation releases could help in the application of an effective management strategy for the control of the cotton mealy bug in the field.
Keywords: Augmentation; Conservation; Instar; Oviposition; Parasitoid